Gesner's Museum of Natural History, An Early Canadian Geological Collection - Miller, Randall; Buhay, Diane (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2007)
In 1842, on the fifth of April, Abraham Gesner opened the doors of his museum in Saint John, New Brunswick to the public. The museum displayed part of his collection of almost 4,000 specimens. His published catalogue included more than 1,200 rocks, minerals and fossils along with a smaller number of invertebrate and vertebrate animals and artefacts. It survives today as one of Canada’s oldest geological collections. This national treasure documents the earliest days of the study of the geological sciences in Canada including specimens from Gesner’s surveys of New Brunswick and Nova Scotia. Although Gesner’s collection moved through three institutions, it has remained partly intact and is accompanied by a catalogue of the museum’s contents.